The stability of the strata overlying the mined-out areas of the central Witwatersrand - F. G. Hill (The Southern African Institute of Mining and Metallurgy, 1981)
The paper reviews the restrictions imposed by the Department of Mines (now the Department of Mineral and Energy Affairs) on the surface use of ground that has been undermined at shallow depths (down to a depth of244m). The reasons for the restrictions are discussed, with special reference to the early records kept by the Department of Mines on subsidence and fracture of the surface. A discussion of the nature of the strata overlying the ore-body, and the effect of undermining, is followed by a detailed account of investigational work, particularly since 1970, on the stability of shallowly undermined ground. The significance of the data collected during the investigations is considered next, with special reference to the social and economic implications. These are so farreaching, that it is proposed that the already flexible approach of the Department of Mineral and Energy Affairs in considering what structures may be built on undermined ground should become even more flexible. To this end, the appointment of a Commission is proposed to collect as much information as possible on the stability of ground undermined at shallow depth, and to revise the current overrestrictive conditions or guide lines that are in use.